2008
DOI: 10.1359/jbmr.080504
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Calcification, BMD, and Bone Microstructure: A Population-Based Study

Abstract: ABSTRACT:To better define the relationship between vascular calcification and bone mass/structure, we assessed abdominal aortic calcification (AAC), BMD, and bone microstructure in an age-stratified, random sample of 693 Rochester, MN, residents. Participants underwent QCT of the spine and hip and high-resolution pQCT (HRpQCT) of the radius to define volumetric BMD (vBMD) and microstructural parameters. AAC was quantified with the Agatston scoring method. In men, AAC correlated with lower vertebral trabecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 89 publications
3
21
0
Order By: Relevance
“…Though limited by the cross-sectional nature of the analysis, this methodology and the reduction in beta estimate we found in our cohort suggest possible causal pathways between variables 19 . This process may particularly apply to the elderly, who are more likely to suffer from weight loss, bone demineralization and vascular calcification 40, 41 . In accordance with this concept, we found a borderline interaction between BMD and age (p=0.07), and after appropriate stratification the role of BMD was confirmed only for individuals older than 68 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Though limited by the cross-sectional nature of the analysis, this methodology and the reduction in beta estimate we found in our cohort suggest possible causal pathways between variables 19 . This process may particularly apply to the elderly, who are more likely to suffer from weight loss, bone demineralization and vascular calcification 40, 41 . In accordance with this concept, we found a borderline interaction between BMD and age (p=0.07), and after appropriate stratification the role of BMD was confirmed only for individuals older than 68 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…32,48 A large number of studies demonstrated a relationship between vascular disease and bone pathology. 4 The coexistence of osteoporosis and vascular calcification has been consistently demonstrated in postmenopausal women and elderly people 49 and also in patients with CKD. 50 This bonevascular axis involves bone-derived proteins that regulate vascular calcification and proteins of vascular origin that regulate bone metabolism.…”
Section: Wnt Inhibitors and The Kidney-bone-vascular Axismentioning
confidence: 99%
“…Dual-energy x-ray absorptiometry (DXA) and central quantitative computed tomography (QCT) can be used to simultaneously quantify BMD and AAC [18, 19]. Although DXA is considered as current clinical gold standard for the diagnosis of osteoporosis and the assessment of fracture risk, this technique has certain limitations.…”
Section: Introductionmentioning
confidence: 99%